Polarization as a probe of neutrino emission from blazars - Paraschos, Georgios Filippos; Traianou, Efthalia; Debbrecht, L. C.; Liodakis, I.; Ros, E. (The astrophysical journal, 2025)
The source of extragalactic neutrinos in the TeV-PeV range is a matter of very active research, with blazar jets having been postulated to be the origin of at least some of the detections. The blazar PKS 0735+178 is a prominent example; during its multiband flare in late 2021, a neutrino event was reported by four observatories, with its origin consistent with the direction of that source. While no new jet component was observed to be ejected during that narrow time frame, our analysis shows that a propagating shock front originating from the core region was the likely source of the multiband flare, using very-long-baseline interferometry images of PKS 0735+178 in polarized light. Taken together, our findings are suggestive of a coherent scenario in which the shock may contribute to the acceleration of protons, with the target photons potentially originating either from the ambient medium surrounding the jet or from proton synchrotron radiation. The necessary conditions for neutrino emission via proton-photon interactions are, hence, present in this jet.